(untitled) (The Conference Hub, 2025)
This article focuses on the epic genre, which is considered the largest of the epic genres, and its translations into other languages. The article discusses the contribution of the German scholar Karl Reichl to this field and his efforts as a scholar who first introduced the epic to a foreign audience.